Potential solution to pollution of groundwater by diffusion of volatile organic compounds through the primary HDPE geomembrane in composite lining systems of landfills - Fourie, W.J. (University of Pretoria, 2016)
Dissertation (MEng)--University of Pretoria, 2015.